Peningkatan Kemampuan Berpikir Kritis Mahasiswa pada Media melalui Film dan Model Discovery Learning - Muh. Bahruddin (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This study aims to determine the increase in critical thinking skills of Visual Communication Design studens at Universitas Dinamika in the mass media. This research focuses on the ability to identify, discover, and solve problems. Researcher used a film medium called "Green Hornet" (2011) by Michel Gondry combined with the discovery learning model. This film tells the story of the production process of the media (newspapers) in the hands of readers. There are interference from media owners, journalists, and other conditions on an issue that will be published by the media. The "discovery learning" model provides an opportunity for students to actively search for, gather, and compile information in order to describe a knowledge. While a lecturer provide data or instructions (models) to find out what students must learn. The lecturer must also review and provide a review of the student's independent learning outcomes. Researcher ask questions that fit the indicators of critical thinking using newspapers and television media. The results of this study were the students' critical thinking skills improved. In cycle 1, students are able to increase their critical power when identifying titles, subtitles, words, phrases, sentences, paragraphs, and captions. While in cycle 2, improvement occurs when students identify images or visuals, tables, charts, and problem solving.